Description of Tik Tok Users Interest in The Issue Of Sexual Violence in The Economic Aspect - Aghnani , Almira Dwi; Abiyudha, Gigih Febrian (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Sexual violence recorded according to data obtained from the Ministry of Women's Empowerment and Child Protection in 2023 in Indonesia reached 25,394 cases. From this figure it was found that as many as 22,331 victims recorded were women and as many as 5,279 victims were men. One of the factors that influence the occurrence of sexual harassment cases is economic factors, in this case, for example poverty. Economic conditions can also be one of the reasons someone commits a crime of decency or rape. Difficult economic conditions will lead people to low education and at a later stage have an impact on whether or not a good job is obtained. In general, people who have a low level of education tend to get inappropriate jobs. With the existence of digital media, especially social media, applications, and websites have become an important and strategic part of the process and results of social, economic, political, and cultural interactions. Digital media changes the way people communicate and socialize in cyberspace. However, digital media can also be used in the learning process, one of which is the TikTok application. The manyfeatures contained in the TikTok application are criteria that can be implemented as a means of delivering educational information, one of which is the content of sexual violence